Efficient spatial allocation of wind power plants given environmental externalities due to turbines and grids - Kristine M. Grimsrud; Cathrine Hagem; Arne Lind; Henrik Lindhjem (Statistics Norway, Research Department, 2020)
Negative environmental externalities associated with wind power plants depend on the physical characteristics of turbine installations and associated power lines and the geographical siting. We derive analytically an environmental taxation scheme for achieving the efficient spatial distribution of new wind power production, taking account of both production and environmental costs. Further, we illustrate the analytical results by means of a detailed numerical energy system model for Norway. We show that a given target for wind power production can be achieved at a significantly lower social cost by implementing a tax scheme, compared to the current situation with no environmental taxes. We also show that the environmental costs associated with both turbines and power lines were crucial to the efficient spatial allocation of wind power plants.
Keywords: H23; Q42; Q48; Q51; 330; Wind power; wind power plant; renewable energy; environmental externalities; environmental taxes; energy system model